2022
DOI: 10.3390/ijerph19042211
|View full text |Cite
|
Sign up to set email alerts
|

Association between Maternal Exposure to Ambient Air Pollution and the Risk of Preterm Birth: A Birth Cohort Study in Chongqing, China, 2015–2020

Abstract: Recent study results on the association between maternal exposure to ambient air pollution with preterm birth have been inconsistent. The sensitive window of exposure and influence level of air pollutants varied greatly. We aimed to explore the association between maternal exposure to ambient air pollutants and the risk of preterm birth, and to estimate the sensitive exposure time window. A total of 572,116 mother–newborn pairs, daily concentrations of air pollutants from nearest monitoring stations were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…Chen et al showed a correlation between SO 2 in late pregnancy and preterm birth [ 40 ], no association was found between SO 2 and preterm birth in early and mid-pregnancy. Zhou et al showed that SO 2 and NO 2 was not associated with preterm birth [ 41 ], which is inconsistent with our findings.A study of air pollutants and preterm birth in California showed that exposure to O 3 was associated with an increased incidence of preterm birth, and also found that the hysteresis effect of O 3 could also increase the incidence of preterm birth [ 42 ], which is inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Chen et al showed a correlation between SO 2 in late pregnancy and preterm birth [ 40 ], no association was found between SO 2 and preterm birth in early and mid-pregnancy. Zhou et al showed that SO 2 and NO 2 was not associated with preterm birth [ 41 ], which is inconsistent with our findings.A study of air pollutants and preterm birth in California showed that exposure to O 3 was associated with an increased incidence of preterm birth, and also found that the hysteresis effect of O 3 could also increase the incidence of preterm birth [ 42 ], which is inconsistent with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…Research data for this study was gathered from a large retrospective cohort of live births from 2015 to 2020, in Chongqing, China, which was consistent with our previously published paper ( 13 ), all birth data were extracted from the birth certificate system database for Chongqing. This database contains maternal age, maternal residence address, date of birth, birth weight, gestational age, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Air pollution exposure assessment was carried out using the same method as our published paper ( 13 ) mentioned above. Based on the detailed residence address of every researched pregnant woman and the location of air monitoring stations, we calculated the distance between each maternal residence and the monitoring sites using ArcGIS (version 10.2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Conversely, the pandemic, particularly during the most extensive lockdowns, has resulted in less pollution and other adverse environmental factors that are considered to be potentially protective of preterm birth. [12][13][14] Nevertheless, the epidemiologic studies that have evaluated the relationship between the COVID-19 pandemic and preterm birth have had inconsistent results. Some have shown no change, some have shown a decreased risk, and some have shown an increased risk of preterm birth after the onset of the pandemic.…”
mentioning
confidence: 99%